Expectational business cycles - Eran A. Guse (Bank of Finland, 2004)
I introduce Expectational Business Cycles where aggregate activity fluctuates due to learning, heterogeneous updating rules and random changes in the social norm predictor.Agents use one of two updating rules to learn the equilibrium values while heterogeneity is dictated via an evolutionary process.Uncertainty of a new equilibrium, due to a shock to the structure of the economy, results in a sudden decrease in output.As agents learn the equilibrium, output slowly increases to its equilibrium value. These business cycles arrive faster, are longer and more severe as agents possess less rationality.
URN:NBN:fi:bof-20140807287
Keywords: C62; D84; E37; 330; adaptive learning; aggregate fluctuations; heterogeneous expectations; multiple equilibria; rational expectations